Microarray bioinformatics - Stekel, Dov (Cambridge University Press, 2003)
DNA microarrays have revolutionised molecular biology and are becoming a standard tool in the field. Unlike traditional molecular biology, the successful use of DNA microarrays requires a substantial use of statistics and computing, to design the arrays, design the experiments, and to analyze and manage the data. This book is written for researchers, clinicians, laboratory heads and managers, from both laboratory and bioinformatics backgrounds, who work, or intend to work with microarrays. It is a comprehensive guide to the mathematics, statistics and computing required to use microarrays successfully.